Desenvolvimento e nodulação de leguminosas arbóreas forrageiras em solos do semiárido potiguar - Costa, Heráclito Lima de Souza (Universidade Federal Rural do Semi-Árido, 2015)
The sabiá (Mimosa caesalpiniifolia Benth.) and the jucá (Caesalpinia férrea Mart. ex. Tul) are species of the leguminosae family and are part of the native vegetation of the northeastern semiarid the Caatinga. The objective of this study was to evaluate the development of the plant and nodulation of arboreal species in different land uses in the Potiguar semiarid. To perform the experiment were collected nine soil samples with different uses: three samples with agricultural cultivation (AC), three samples of native forest (NF) and three samples with degradation characteristics (DE). Physical analysis and soil chemistry were made, and also processed and distributed in bags of seedlings with 5L capacity, with one plant per bag. The experiment was conducted in a greenhouse. The harvest of the experiment was performed 90 days after the transplanting. The variables analyzed were: plant height (PH), stem diameter (SD), dry matter of the aerial part (DMAP), root dry weight (RDW), dry matter of the whole plant (DMWP) and number of nodes (NN). The experimental design was completely randomized, with 9 treatment and 3 repetitions. We found a smaller SD, DMAP, RDW and DMWP in NF2 soils, DE1 and DE2 to the sabiá. For the jucá the lowest growth of plants was in NF2 and DE2 soils. The sabiá presented nodulation in all soils, while the jucá not formed any nodule. Soils with degradation characteristics provided the sabiá greater number of nodes than the agricultural soils and native vegetation
Development and nodulation legumes tree forage in the soil semiarid potiguar
Keywords: Caatinga; Jucá; Sabiá; Fertilidade do solo; Caatinga; Jucá; Sabiá; Soil fertility; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL